Interactive Effects of Potassium and Salt Stress on Selected Physiological Traits in Two Sunflower (Helianthus annuus L.) Cultivars - Zinah Al-Hatab; elakeili, aida; Saber, Nabil; Mostafa, Eazaz; Hassan , Atiat (AlQalam Journal of Medical and Applied Sciences, 2025)
Salinity is considered one of the most important factors that limit plant growth and production through its adverse effects on physiological and biochemical processes in plant cells. It is noteworthy that the physiological response of salt-stressed plants varies according to the plant species and cultivars, as well as the type and salt concentrations. The sterilized sunflower seeds were transferred to plastic pots (15 cm in diameter, 20 cm length with a hole at the bottom) filled with a fixed amount of previously acid-washed quartz sand. The water holding capacity was kept at 80% during the whole experimental period. The pots were divided into two sets: first set was irrigated with 1/10 strength modified Hoagland solution (adequate K+, 6 mM) supplemented with 0, 20, 50 and 100 mM NaCl, while the second set was irrigated with 1/10 Hoagland solution supplemented 0, 20, 50 and 100 mM NaCl in presence of with double K+ concentration (double K+ concentration, 12 mM). At 25 d, homologous samples (of two sunflower cultivars) were harvested, dissected into leaves and roots, and quickly saved for estimation of the various chemical analyses.